The social and clinical impact of the COVID‐19 epidemic on the Strasbourg lung transplant cohort: A single‐center retrospective cohort study. Issue 12 (26th October 2020) - Renaud‐Picard, Benjamin; Gallais, Floriane; Riou, Marianne; Chatron, Eva; Degot, Tristan; Freudenberger, Sophie; Porzio, Michele; Schuller, Armelle; Stauder, Julien; Hirschi, Sandrine; Kessler, Romain
Abstract: The clinical and social impacts of the COVID‐19 epidemic on lung transplant (LTx) recipients remain poorly known. We aimed to evaluate its social, clinical, and behavioral consequences on the LTx patients followed in Strasbourg university hospital. A questionnaire was used to collect details concerning patients' lifestyles, their protection methods used to avoid COVID‐19 contamination, and clinical infection‐related information for March 2020. A specific score was created to quantify patients' contacts and the associated risk of infectious contagion. Data were collected from 322 patients (91.2%). A majority reported a higher application than usual of social distancing and barrier measures. 43.8% described infectious‐related symptoms and 15.8% needed an anti‐infective treatment. There was no difference in symptom onset according to age, native lung disease, diabetes, or obesity. Nineteen patients were tested for COVID‐19, and four were diagnosed positive, all with a favorable outcome. The infection risk contact score was higher for symptomatic patients (p: 0.007), those needing extra‐medical appointments ( p < .001), and those receiving anti‐infective treatments ( p = .02). LTx patients reported a careful lifestyle and did not seem at higher risk for COVID‐19. Our score showed encouraging preliminary results and could become a useful tool for the usual infection‐related follow‐up of the LTx patients.